The Socio-Educational Value of Sekar Jepun Dance - Sugita, I Wayan; Pastika, I Gede Tilem (Graduate School of Institut Seni Indonesia Yogyakarta, 2024)
This article aims to describe the form of the Sekar Jepun dance, the mascot of Badung Regency, and its socio-educational values. This article is qualitative research in the field of cultural arts. The research data were collected through observation, documentation study, and in-depth interviews with several informants, namely the Sekar Jepun dance actors, Badung district government officials, and Balinese arts and culture observers. Qualitative descriptive analysis was carried out by applying aesthetic theory and semiotics. The results showed that first, the Sekar Jepun dance had the theme of majesty sourced from the natural environment, namely the Jepun tree. The form of the Sekar Jepun dance as the mascot of Badung Regency is reflected in its complete performance, including dance performers, gamelan accompaniment, makeup and clothing, performance venues, and Sekar Jepun dance performance structures, namely papeson (head), pangawak (body), pangecet and pakaad. (feet). This dance is performed at various official moments in the Badung Regency, Bali. Second, the Sekar Jepun dance contains noble values, including aesthetic, religious, and socio-educational values that follow the Tri Hita Karana philosophy. Nilai Pendidikan Sosial pada Tari Sekar Jepun Abstrak Artikel ini bertujuan untuk mendeskripsikan bentuk tari Sekar Jepun, maskot Kabupaten Badung, dan nilai-nilai pendidikan sosialnya. Artikel ini merupakan penelitian kualitatif di bidang seni budaya. Data penelitian dikumpulkan melalui observasi, studi dokumentasi, dan wawancara mendalam dengan beberapa informan, yaitu pelaku tari Sekar Jepun, pejabat pemerintah kabupaten Badung, dan pemerhati seni dan budaya Bali. Analisis deskriptif kualitatif dilakukan dengan menerapkan teori estetika dan semiotika. Hasil penelitian menunjukkan bahwa pertama, tari Sekar Jepun bertemakan keagungan yang bersumber dari lingkungan alam, yaitu pohon Jepun. Bentuk tari Sekar Jepun sebagai maskot Kabupaten Badung tercermin dari pertunjukannya yang lengkap, meliputi penampil tari, pengiring gamelan, tata rias dan pakaian, tempat pertunjukan, dan struktur pertunjukan tari Sekar Jepun, yaitu papeson (kepala), pangawak (badan), pangecet dan pakaad. (kaki). Tarian ini ditampilkan pada berbagai momen resmi di Kabupaten Badung, Bali. Kedua, tari Sekar Jepun mengandung nilai-nilai luhur, meliputi nilai-nilai estetika, agama, dan pendidikan sosial yang mengikuti falsafah Tri Hita Karana.